Sistem Penerimaan Badan Ad Hoc Panitia Pemilihan Kecamatan dalam Pemilihan Kepala Daerah pada Komisi Pemilihan Umum Kota Medan - Syafitri, Ririn; Muda, Indra; Matondang, Armansyah (Universitas Medan Area, 2019)
Election is a way to choose a leader or people representative's and the only mechanism of power change in Indonesia. In it's relation with the election for district head and vice district head, the commitee's existence is included in the constitution of Indonesia number 7 2017 about the Election's Commitee. Therefore, it can be said that the Commitees determines the good and the bad in an election. Ad hoc acceptance system is one of the process in the General Election Commision in Medan for filtering the candidate for the Election's Commitee. ?According to the General Election Commision Criteria to be the Election's commitee. Usually, the ad hoc acceptance system begin with announcement, registration, test and acceptance. Because of that, the General Election Commision need help from the public to participate in the Election. The purpose of this Observation is to know the ad hoc acceptance system to elect the district head and vice district head.?